Stretchable distributed fiber-optic sensors - Bai, Hedan; Li, Shuo; Barreiros, Jose; Tu, Yaqi; Pollock, Clifford R.; Shepherd, Robert F. (Science (American Association for the Advancement of Science), 2020)
Distributed fiber-optic sensors have been used for monitoring mechanical deformations in stiff infrastructures such as bridges, roads, and buildings, but they either are limited to measuring one variable or require complex optics to measure multiple properties. Bai et al. now demonstrate dual-core elastomeric optical fibers, one of which contains patterned dye regions. The waveguides are fabricated by molding out of commercially available elastomers and integrate a clear core and an adjacent core doped with up to three macroscale dye regions. Changes in optical paths in the two cores detect deformation and map it onto a color space. By monitoring changes in the color and intensity in both elastomer-based fibers, the researchers could distinguish bending, stretching, and localized pressing with a spatial resolution down to ∼1 centimeter. Science , this issue p. 848 A stretchable optomechanical sensor decouples deformation types, detects locations, and measures deformation magnitudes. Silica-based distributed fiber-optic sensor (DFOS) systems have been a powerful tool for sensing strain, pressure, vibration, acceleration, temperature, and humidity in inextensible structures. DFOS systems, however, are incompatible with the large strains associated with soft robotics and stretchable electronics. We develop a sensor composed of parallel assemblies of elastomeric lightguides that incorporate continuum or discrete chromatic patterns. By exploiting a combination of frustrated total internal reflection and absorption, stretchable DFOSs can distinguish and measure the locations, magnitudes, and modes (stretch, bend, or press) of mechanical deformation. We further demonstrate multilocation decoupling and multimodal deformation decoupling through a stretchable DFOS–integrated wireless glove that can reconfigure all types of finger joint movements and external presses simultaneously, with only a single sensor in real time.